Novel solutions to the coupled KdV equations and the coupled system of variant Boussinesq equations - Yao, Shao-Wen; Zafar, Asim; Urooj, Aalia; Tariq, Benish; Shakeel, Muhammad; İnç, Mustafa (Elsevier, 2023)
This article examines the coupled KdV equations and the coupled system of variant Boussinesq equations with beta time derivative and explores their travelling wave solutions. This work explains the evolution of waves with fractional parameter. The simple ansatz approach produces a variety of novel solutions in terms of hyperbolic and periodic functions. Graphical representation of solutions are also presented.
Keywords: Travelling wave solutions; Coupled KdV equations; System of variant Boussinesq equations